Methylxanthine Treatment in Patients Hospitalized for Acute Exacerbation of Chronic Obstructive Pulmonary Disease in China: A Real-World Study Using Propensity Score Matching Analysis - Zhan, Zijie; Ma, Yiming; Huang, Ke; Liang, Chen; Mao, Xihua; Zhang, Yaowen; Ren, Xiaoxia; Lei, Jieping; Chen, Yan; Yang, Ting; Wang, Chen (Frontiers in Pharmacology, 2022)
Abstract Background: Although medical guidelines discourage the use of methylxanthines in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD), they are still widely used in clinical practice. This study investigated the real-world use of methylxanthines in the management of AECOPD. Methods: Patient data from the Acute exacerbation of Chronic obstructive pulmonary disease Using REgistry data (ACURE, NCT02657525) study database were screened. Enrolled patients were divided into treatment and control groups. Propensity score (PS) matching and Cox regression analyses were used to minimize confounding factors and determine the association between methylxanthine treatment and the length of stay (LOS). Results: Among the 2088 eligible patients, 1563 (74.9%) were in the methylxanthine treatment group. Patients treated with methylxanthines had more severe respiratory symptoms and worse lung function than those in the control group. Doxophylline was the most commonly used methylxanthine in both secondary and tertiary hospitals. After PS matching, 966 patients were equally divided into two groups. The LOS of patients in the two groups was similar (median: 8 days, interquartile range [IQR]: 7–11 days, p=0.730). Patients in the treatment group (median: 8, IQR: 4–12) had a more significant decrease in the COPD Assessment Test score from admission to discharge than those in the control group (median: 6, IQR: 2–10, p <0.001). Among all matched patients, the LOS was not significantly associated with methylxanthine treatment (adjusted hazard ratio [HR]: 1.02, 95% confidence intervals [CIs]: 0.89–1.16). However, in the subgroup analysis, methylxanthines were significantly associated with a short LOS in patients with blood eosinophil count > 4% (adjusted HR: 1.56, 95% CIs: 1.12–2.17). Conclusions: This study revealed that methylxanthines, especially doxophylline, are widely used in China. Methylxanthines were effective in improving symptoms in AECOPD patients. Higher blood eosinophil count may be associated with a better efficacy of methylxanthine treatment.